The internet AS-level topology three data sources and one definitive metric. - Mahadevan, Priya
We calculate an extensive set of characteristics for Internet AS topologies extracted from the three data sources most frequently used by the research community: traceroutes, BGP, and WHOIS. We discover that traceroute and BGP topologies are similar to one another but differ substantially from the WHOIS topology. Among the widely considered metrics, we find that the joint degree distribution appears to fundamentally characterize Internet AS topologies as well as narrowly define values for other important metrics. We discuss the interplay between the specifics of the three data collection mechanisms and the resulting topology views. In particular, we how how the data collection peculiarities explain differences in the resulting joint degree distributions of the respective topologies. Finally, we release to the community the input topology datasets, along with the scripts and output of our calculations. This supplement hould enable researchers to validate their models against real data and to make more informed election of topology data sources for their specific needs
Keywords: Computer systems organization; Computer communication networks; Local and wide area networks; Internet (e.g., TCP/IP).; Network architecture and design; Network topology; Mathematics of computing; Discrete mathematics; Graph theory; Network problems; Probability and statistics; Distribution functions; Multivariate statistics; Correlation and regression analysis